(untitled) (Medico Legal Update, 2020)
Background: Preschool screenings are recommended for early detection and treatment of childhood visual and hearing disorders. Objective: To evaluate the prevalence of hearing abnormalities, visual impairments and correlate its association with consumption of vitamin A rich food and usage of electronic devices in school going children in Udupi district, Karnataka Method: Rinnie’s test and Weber’s tests was done by using tuning fork method for hearing, Snellen’s chart for distant vision, Jager’s chart for near vision, Ishiara chart for colour vision and confrontation test for field of vision. Questionnaires were used to get the detailed informations regarding consumption of vitamin A rich food and usage of electronic devices, Result: Screening test for hearing and vision conducted on 250 students. There was no significant hearing abnormality was found out of 250 students, there was hearing impairment in 1.6% of the children due to ear infection. In vision screening,12.8% of children having visual abnormalities like myopia, hyperopia and color blindness. The total prevalence of vision abnormalities was 32(12.8%) 95% CI: 11.924-13.676. Conclusion: Vision and hearing screening is very essential in school children to recognize the visual impairments or hearing abnormalities at earliest which will be helpful for further treatment. This study should be conducted in large sample size.